2009
DOI: 10.7326/0003-4819-150-2-200901200-00003
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Prediction With and Without Knowledge of Genetic Variation at Chromosome 9p21.3

Abstract: Background While genetic variation at chromosome 9p21.3 is associated with incident cardiovascular disease (CVD), it is unclear whether screening for this polymorphism improves risk prediction. Objective To determine whether knowledge of variation at chromosome 9p21.3 provides predictive information beyond that from other readily available risk factors. Design Prospective cohort study Setting United States Patients 22,129 female Caucasian health professionals participating in the Women's Genome Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
147
0
5

Year Published

2009
2009
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(156 citation statements)
references
References 23 publications
4
147
0
5
Order By: Relevance
“…(41) Empirically, it has been shown that the incorporation of genes did not result in an appreciable increase in the accuracy of the prognosis of type 2 diabetes (42) and cardiovascular diseases, (39,40) which suggests that common genetic variants have a minimal effect on the prognosis of these diseases. However, the mentioned work assessed the incremental prognostic value based on the AUC rather than the reclassification analysis as in our work.…”
Section: Discussionmentioning
confidence: 99%
“…(41) Empirically, it has been shown that the incorporation of genes did not result in an appreciable increase in the accuracy of the prognosis of type 2 diabetes (42) and cardiovascular diseases, (39,40) which suggests that common genetic variants have a minimal effect on the prognosis of these diseases. However, the mentioned work assessed the incremental prognostic value based on the AUC rather than the reclassification analysis as in our work.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the question was then posed as to the relative importance of this one marker in clinical risk prediction. In both a prospective cohort study of white women 49 and a meta-analysis of possible clinical utility, 50 knowledge of the 9p21 genotype added little or nothing to traditional risk factor assessment. The Evaluation of Genomic Applications in Practice and Prevention Working Group recently evaluated 9p21 and 57 other genetic variants linked by GWAS to coronary artery disease and "… found that the magnitude of net health benefit from use of any of these tests alone or in combination is negligible. "…”
mentioning
confidence: 99%
“…The association of the 9p21.3 locus with conditions such as dementia [33] and stroke [34] may indicate a role in a common mechanism of disease, rather than specifically CAD. Incorporation of 9p21.3 and other risk-conferring alleles into a CAD prediction algorithm still performs worse than current models, based on clinical parameters [35], or provide no additional benefit [36], despite the availability of 9p21.3 genotyping via the internet. The 9p21.3 locus, although undoubtedly hugely exciting, remains therefore to be substantiated in terms of its true importance.…”
Section: Genome-wide Association Studies: Getting Closer To the Genetmentioning
confidence: 97%